USING VOICE COMMANDS TO OBTAIN EXPRESSIVE STATES FOR ANIMATRONIC STRUCTURES - Marian IONESCU (Fiabilitate şi Durabilitate)
This paper presents an experiment that uses voice control applied to animatronic structures as well as a robotic structure. Voice control is applied in order to obtain biomimetic / expressive states through animatronic structures (CHIMPANZEE ALIVE and ELVIS ALIVE), using a interactive protocol with the robotic structure (LOBOT uHand). The interactive protocol involves the interaction and implementation of sequential actions performed by robotic structures, which depend on the effect of voice commands and the interpretation of the colors of objects.